PHARMACEUTICS & THERAPEUTICS OF KAJJALI (BLACK SULPHIDE OF MERCURY) - A REVIEW - Ranjeet, Sawant; Manish, Bhoyar (Asian Journal of Pharmaceutical Research and Development, 2013)
Rasashastra has been using herbo-mineral metallic preparations in therapeutics since decades. Rasashastra texts does not advised single use of Mercury because of its two distinct properties namely quickness & liquid state. To surmount these intricacies Scholars mentioned certain mercury bonding procedures (Kajjali Bandha), one of them is Kajjali Bandha. The fine black powder obtained from pounding of mercury with metals, sulphur & other substances, without the addition of any liquid substance is known as Kajjali. Most of Rasashastra formulations used Kajjali as fundamental ingredient. Different Khalvi Rasayana (drugs prepared in mortar & pestle) has been reviewed to identify percentage of Kajjali in single dose. Present article is focused on manufacturing, analysis & therapeutics & toxicological aspect of Kajjali.